PENDEKATAN DIAGNOSIS DAN MANAJEMEN CHOREA PADA KONDISI HIPERGLIKEMIA HIPEROSMOLAR NON KETOTIK: LAPORAN KASUS - Valentina Tjandra Dewi; Sri Yenni Trisnawati; Dewa Putu Gde Purwa Samatra (PERDOSNI, 2021)
Abstract Introduction: Chorea can be classified based on its etiology as primary and secondary chorea. Primary chorea is idiopathic/genetic, while secondary chorea is associated with infections, metabolic, endocrine, and immune disorders, or drug-induced. One of the metabolic disorders that can manifest as chorea is hyperglycemic state, which is commonly found in people with uncontrolled diabetes mellitus. Case Report: A 70-year-old man came to the emergency room with involuntary and irregular movements which appeared like dancing movements along his left upper limb. The patient had a history of uncontrolled type-2 diabetes mellitus (DM) and it was known that the blood glucose result on admission was 926 mg / dL and HbA1C 15.4%. Blood glucose regulation was carried out by the endocrinology department with rehydration and administering intravenous rapid acting insulin infusion, later on, the chorea symptoms disappeared within 24 hours after glycemic control and adding of dopamine antagonist drug. Discussion: Hyperglycemia can impair perfusion of the contralateral striatum and disrupt Gamma Amino Butyric Acid (GABA) resulting in excessive inhibition of the subthalamic nucleus and hyperexcitation of the thalamocortical system. When diagnosing chorea, a comprehensive evaluation of patient history, neurological examination, laboratory tests, and imaging are essential. Management of chorea relies on the identification of underlying etiology. Conclusion: Most cases of chorea or hemichorea induced by non-ketotic hyperglycemia have a good prognosis. Blood glucose regulation is the mainstay of therapy, while dopamine receptor antagonist drugs are sometimes required in cases where symptoms are not fully improved. Keywords: chorea, non ketotic hyperglycemia, involuntary movements